T-cassette ligation: a method for direct sequencing and cloning of PCR-amplified DNA fragments. - Iwahana, H; Yoshimoto, K; Tsujisawa, T; Itakura, M

(untitled) (Genome Research, 1994)
We describe a method to ligate a PCR-amplified DNA fragment with T-protruding cassettes, which have multiple sites for endonuclease, promoter sequences of T3 and T7, and annealing sites for the universal M13 forward and reverse primers. This method, which we named T-cassette ligation, substantially facilitated direct sequencing and subcloning of PCR products. Two T-cassettes with a protruding T at their 3' ends were obtained by annealing adaptor oligomers to XbaI- or XhoI-digested pBluescript. A DNA fragment amplified by the first PCR was ligated separately to one of the two T-cassettes. The second PCR was performed using a primer complementary to one of the two T-cassettes and one of the two primers used for the first PCR to amplify the ligation product in low abundance. The resultant two DNA fragments had the T3 and T7 promoter, and an annealing site for the universal M13 forward and reverse primer, respectively. These DNA fragments were applicable to direct sequencing. For the purpose of subcloning, the third PCR was carried out with two primers each complementary to each of two T-cassettes and two PCR-amplified DNAs by the second PCR, as templates. The PCR product of the third PCR had multiple sites of the pBluescript polycloning site at both ends, facilitating its subcloning into pBluescript.